Change in heart rate variability during two firefighting work cycles. Issue 2 (3rd April 2023) - Gendron, Philippe; Laurencelle, Louis; Lajoie, Claude; Trudeau, François; Houle, Julie; Goulet, Éric D. B.
Abstract : This study aimed to determine whether the change in heart rate variability from pre to post firefighting is modulated by different work cycles. Thirteen male firefighters underwent two firefighting simulations that comprised two identical 25-min work bouts intercalated by a passive recovery period of either 20 min (T20) or 5 min (T5). The square root of the mean squared differences of successive R–R intervals (RMSSD) and aural temperature were measured at rest before (PRE) and after (POST) firefighting simulations. The decrease in RMSSD was different between firefighting simulations (T20: −10 ± 21.2 ms, T5: −19.9 ± 20.9 ms, interaction, p  = 0.02). Post-firefighting aural temperature was greater ( p  = 0.05) in T5 (37.18 ± 0.53 °C) than in T20 (36.88 ± 0.49 °C). In conclusion, a shorter recovery period of 5 min between firefighting work bouts decreases post-firefighting heart rate variability, possibly attributed to a lower parasympathetic reactivation and a higher absolute value of body temperature.